Identification and characterization of HMBS gene mutations in spanish patients with acute intermittent porphyria - Méndez, M; Morán-Jiménez, M J; Gomez-Abecia, S; Garcia-Bravo, M; Garrido-Astray, M C; Fontanellas, A; Poblete-Gutiérrez, P; Frank, J; Enriquez De Salamanca, R (Cellular and Molecular Biology, 2009)
Acute intermittent porphyria (AIP), the most common acute hepatic porphyria, is an autosomal dominant disorder with low penetrance that results from a partial deficiency of hydroxymethylbilane synthase (HMBS), the third enzyme in the heme biosynthetic pathway. The disease is clinically characterized by acute neurovisceral attacks that are precipitated by several factors including certain drugs, steroid hormones, alcohol and fasting. Early diagnosis and counselling are essential to prevent attacks, being mutation analysis the most reliable method to identify asymptomatic carriers in AIP families. In this study we have investigated the molecular defect in 15 unrelated Spanish AIP patients. Mutation analysis of the HMBS gene revealed a total of fourteen mutations including six novel ones, two of them were on the same allele in one patient. The novel mutations were three missense (R26L, R173G and D178H), two frameshift (c.749_765dup and c.874insC) and one intronic deletion (IVS12+3_+11delAGGGCCTGT). RT-PCR and sequencing demonstrated that the intronic mutation caused abnormal splicing and exon 12 skipping. Prokaryotic expression of the novel missense mutations showed that only D178H had significant residual activity. These findings will facilitate the accurate identification of presymptomatic AIP carriers in these families and they further emphasize the molecular heterogeneity of AIP in Spain.